Girls, identities and agency in adolescents’ digital literacy practices - Koutsogiannis, Dimitrios; Adampa, Vassiliki (Journal of Writing Research, 2012)
This paper focuses on the ways girls use digital environments, like Word, PowerPoint and chatting programmes, for writing and communication purposes. By combining quantitative and qualitative methods of analysis and by adopting a critical discourse framework, we will explore the relationship between girls and new media, especially the ones related to digital writing, in terms of three interconnected variables. The first one is related to the role of the two most important socialisation institutions, home and school, at the present historical juncture, characterised by intense mobility and an expansion of traditional forms of literacy. The strategic choices of the girls’ families and their schools’ teaching practices contributed significantly to the formulation of their digital writing practices. The second variable is gender. Our data clearly show that a substantial number of girls were more inclined than their male peers to use word-processing and presentation software, performing, thus, the school discourses of ’diligent students’. The third key variable concerns the personality of the girls who filtered in their own unique ways their social experiences, overcame limitations, took initiatives and appropriated technologically-mediated writing media for personally meaningful ends that enhanced their school and/or entertainment Discourses.